2015
DOI: 10.1177/1527002515588135
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation in the UEFA Champions League

Abstract: This paper aims to evaluate the performance of the most significant football teams in Europe. In particular, we have selected all the teams who have participated in the UEFA Champions League (UCL) during the last nine seasons (2004/05 to 2012/13): 94 different clubs in total. We have applied the Data Envelopment Analysis (DEA), a deterministic non-parametric frontier method usually developed in efficiency studies. To solve the problem of measuring sporting results as output in knockout competitions we have pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
(99 reference statements)
2
26
0
3
Order By: Relevance
“…() argued that the performance of a player may be affected by the level of efficiency of the club employing him. The authors showed that, within the UEFA Champions League, clubs often hamper a player achieving his full potential, or choose inappropriate sports tactics (Zambom‐Ferraresi et al ., ). Again at the team level, McNamara et al .…”
Section: Theory Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…() argued that the performance of a player may be affected by the level of efficiency of the club employing him. The authors showed that, within the UEFA Champions League, clubs often hamper a player achieving his full potential, or choose inappropriate sports tactics (Zambom‐Ferraresi et al ., ). Again at the team level, McNamara et al .…”
Section: Theory Model and Hypothesesmentioning
confidence: 99%
“…Several studies have illustrated how a player's performance may be affected by team-level factors. For example, Zambom-Ferraresi et al (2017) argued that the performance of a player may be affected by the level of efficiency of the club employing him. The authors showed that, within the UEFA Champions League, clubs often hamper a player achieving his full potential, or choose inappropriate sports tactics (Zambom-Ferraresi et al, 2017).…”
Section: Partial Mediation Model Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Concerning supranational competitions, the UEFA Champions League is the world's top competition at football club level, and efficiency studies are really scarce in this area (as examples we can find García-Cebrián, 2010, andZambom-Ferraresi, García-Cebrián, Lera-López, &Iráizoz, 2017). The fact that the sample comprises an unbalanced panel data set and the limited availability of data could be some reasons for this shortage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They take the following as outputs: wins, goals scored, points won, position achieved in the Spanish league competition, points not won out of the total possible points. The inputs used are those related to the performances of the players in different tasks or tasks inherent to the individual and collective ability, fitness and experience of the players [8,24]: shots at a goal, minutes of possession, recoveries of the ball made, crosses made into the area of the opposition [28], and other technical elements of the game. Other studies use economic-financial information and they take the following as inputs and outputs: the cost of the primary resource (players) or depreciation charges as a supposed measure of the abilities of the players to achieve sporting performance; the influence of these and other costs on total revenue; wages and transfer spending and sales [29]; personnel costs [30] or net profit [31].…”
Section: Research In Efficiency In Football Teamsmentioning
confidence: 99%